Pendekatan Strategis dalam Manajemen Pendidikan Islam Kontemporer - Sriwiji Lestari; Muhammad Husni (Jurnal Wahana Literasi Pendidikan, 2026)
This study aims to examine the strategic approach in contemporary Islamic education management through the integration of Islamic values and modern management principles. The method used is library research with content analysis of relevant and up-to-date primary and secondary sources. The findings indicate that the strategic approach in Islamic education management encompasses four main dimensions: itqan-based planning, syura-based organizing, amanah-based implementation, and tawazun-based evaluation. The integration of Islamic values and modern management produces a governance model that is both effective and spiritually meaningful. This study concludes that Islamic educational institutions adopting an integrative strategic approach prove to be more adaptive and competitive in the contemporary era.